Hubungan Kualitas Tidur, Tingkat Stress, Dan Pola Makan Terhadap Kejadian Gastroesophageal Reflux Disease pada Mahasiswa di Yogyakarta - Munada Madalia Hasuna; Adhila Fayasari (Universitas Airlangga, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is a prevalent digestive disorder among university students. The factors included impaired lifestyle habits, including inadequate sleep, elevated stress, and unhealthy eating patterns. Objective: To examine the correlation between sleep quality, stress levels, and eating patterns with the incidence of GERD among university students in Yogyakarta. Methods: A cross-sectional study was conducted from January to April 2025 in PGRI Yogyakarta University, involving 410 university students. We used validated questionnaires for data collection, including the GERD-Q, the Pittsburgh Sleep Quality Index (PSQI), the Depression, Anxiety, and Stress Scales (DASS-21), and an eating pattern questionnaire. We used chi-square tests and correlation tests with a 5% level of significance for the statistical analysis. Results: About 20% of respondents were identified as having GERD symptoms. Students with poor sleep quality were 2.94 times to develop GERD (p=0.001). There was a strong association between stress levels and GERD (p<0.001; r=0.382). Students who have disordered eating were 3.2 times more likely to get GERD (p=0.000). Conclusion: The prevalence of GERD among university students is significantly associated with poor sleep quality, increased stress levels, and disordered eating patterns. Health education aimed at promoting lifestyle changes plays a crucial role in preventing GERD among university students.